Estudo da resposta termicamente estimulada do compósito LDPE/CB por meio da técnica de corrente de despolarização termicamente estimulada (TSDC) - Kowalski,Edemir Luiz (2009)
The thermally stimulated depolarization current (TSDC) in a range of temperature from 84 to 373 K, has been applied to study the depolarization current of polyethylene and polyethylene composites in form of film and filled with commercial or oxidative surface treatment carbon black. The diagrams of TSDC obtained show that the composite in which the carbon black had received oxidative surface treatment reducing on an average depolarization current intensity in a magnitude order if compared to the composite with commercial carbon black. Therefore in the area between α and β transitions the difference is accentuated by reaching a peak 55 times in a temperature of 240 K. The difference in results is explained in terms of molecular interactions neighboring of carbon black particles.